2015 IEEE Conference on Computer Vision and Pattern Recognition (CVPR) 2015
DOI: 10.1109/cvpr.2015.7298975
|View full text |Cite
|
Sign up to set email alerts
|

Metric imitation by manifold transfer for efficient vision applications

Abstract: Metric learning has proved very successful. However, human annotations are necessary. In this paper, we propose an unsupervised method, dubbed Metric Imitation (MI), where metrics over cheap features (target features, TFs) are learned by imitating the standard metrics over more sophisticated, off-the-shelf features (source features, SFs) by transferring view-independent property manifold structures. In particular, MI consists of: 1) quantifying the properties of source metrics as manifold geometry, 2) transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 41 publications
0
52
0
Order By: Relevance
“…We are also aware that there are some works proposed for solving the tasks in which training and test data contains different information, which are less related to SVM+ [2,3,5,7,13,14,15,20,30,35].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We are also aware that there are some works proposed for solving the tasks in which training and test data contains different information, which are less related to SVM+ [2,3,5,7,13,14,15,20,30,35].…”
Section: Related Workmentioning
confidence: 99%
“…For example, the training images of many datasets for image recognition are annotated with privileged information such as attributes, object bounding boxes, textual descriptions, depth information. Although the raw test images in the real-world applications are not associated with such information, it has been demonstrated that such information is useful for learning classifiers with better recognition performance [5,11,20,29,32,33,35].…”
Section: Introductionmentioning
confidence: 99%
“…We conduct experiments on various popular applications: scene classification, object recognition, image retrieval and face verification. In addition to the Euclidean (EU) and single domain DML baselines, we further compare with several representative heterogeneous transfer learning approaches that could learn distance metric [5], [15], [17], [18]. The results validate the effectiveness of the proposed HTDML.…”
Section: Introductionmentioning
confidence: 87%
“…There exists a recent work of metric imitation [5], which learns an improved distance metric for the target features by utilizing them to approximate the manifold of source domain. It is more flexible than the other HTL approaches since the graph of the source domain can be computed offline, but the solution is obtained by performing eigenvalue decomposition on a large size graph matrix.…”
Section: Heterogeneous Transfer Learningmentioning
confidence: 99%
“…In [10], a metric was learnt to make the k-nearest neighbors belonging to the same class separated from examples in other classes by a large margin. In [11], a distance metric over cheap features was learned by the supervision of standard metric over more sophisticated source features.…”
Section: Related Workmentioning
confidence: 99%